The Indians of Texas : from prehistoric to modern times - Newcomb, William W. (William Wilmon), 1921-2010; Story, Hal M.; James H. Sutton Jr. and Sylvia Leal Carvajal Collection (Austin, TX : University of Texas Press, 1961)
Anthropological study of the Comanches, Wichitas, Tonkawas and other Texas Indian societies.
Before the written record. The beginnings -- Savages of the Western Gulf culture area. The Coahuiltecans : South Texas ; The Karankawas : Gulf Coast -- Nomads of the plains. From foot to horse ; The Lipan Apaches : conquerors dispossessed ; The Tonkawas : Central Texas ; Comanches : terror of the Southern Plains ; Kiowas and Kiowa Apaches : far-ranging raiders -- Barbaric gardeners. The Jumanos : southwestern borders ; The Wichitas : nations of the north ; The Caddo confederacies : East Texas ; The provincial Atakapans -- Bitter bread of banishment. Extermination and oblivion.
Includes bibliographical references (pages 365-377) and index.
Buckingham Books
Indian Rights Association Complimentary Collection.
Keywords: Indians of North America -- Texas; Texas -- History; Karankawa Indians; Cahuilla Indians; Kiowa Indians; Jumano Indians; Tonkawa Indians; Lipan Indians; Comanche Indians; Apache Indians; Wichita Indians; Caddo Indians; Texas -- History -- 19th century; Karankawa Indians; Indiens d'Amérique -- Texas; Cahuilla (Indiens); Kiowa (Indiens); Jumano (Indiens); Tonkawa (Indiens); Lipan (Indiens); Comanche (Indiens); Apache (Indiens); Wichita (Indiens); Caddo (Indiens); 1800-1899; Apache Indians; Caddo Indians; Cahuilla Indians; Comanche Indians; Indians of North America; Jumano Indians; Karankawa Indians; Kiowa Indians; Lipan Indians; Tonkawa Indians; Wichita Indians; Texas; Indians of North America -- Texas; Cahuilla Indians; Karankawa Indians; Kiowa Indians; Jumano Indians; Tonkawa Indians; Lipan Indians; Comanche Indians; Apache Indians; Wichita Indians; Caddo Indians; United States, Texas -- Native races; United States, Texas -- History -- 19th century; Indians of North America -- Texas; Indians of North America -- History; History